If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x-12-5x=x+3+x
We move all terms to the left:
2x-12-5x-(x+3+x)=0
We add all the numbers together, and all the variables
2x-5x-(2x+3)-12=0
We add all the numbers together, and all the variables
-3x-(2x+3)-12=0
We get rid of parentheses
-3x-2x-3-12=0
We add all the numbers together, and all the variables
-5x-15=0
We move all terms containing x to the left, all other terms to the right
-5x=15
x=15/-5
x=-3
| 2x-122x-12-5x=x+3+x | | 2(4w+5)/5=9 | | 20x-20+12x=14-2x | | 3x-11=69 | | 3r-12-8r+210=180 | | 1/8(x-10)=4+x | | -2(7x+6)=-12-14x | | 3x=4+28 | | 4(m-1)=8(m-1)+12 | | 9v+54=18v | | y/10-3=5 | | x+24+2x=2-2x-4 | | -5-19p=-17p-13-2p | | 1(2y+-1)=-9 | | 6+15x=-3(-5x-2) | | -8u-8=-4(u+6) | | 8(s-3)=-84 | | 4+2x=2(-x+2)-8 | | b-4/2=b+1/4 | | 6+15x=-3 | | 6-4n=-409 | | -14x+11-11=-17-14x | | 6-4n=-409 | | 3x-4-4x=3x-4-2x-6x | | -20+x=20+20-9x | | 48=-v+188 | | 36-x=192 | | -8x-19=-4-15-8x | | 7x-17=x+6+x+2 | | 7x-12.73=6x+12.27 | | 5-c/8=10 | | 98=-y+223 |